Raman Gas Sensor for Hydrogen Detection via Non-Dispersive and Dispersive Approaches - Fabio Melison; Lorenzo Cocola; Luca Poletto (Sensors)
The current solicitude in hydrogen production and its utilization as a greenhouse-neutral energy vector pushed deep interest in developing new and reliable systems intended for its detection. Most sensors available on the market offer reliable performance; however, their limitations, such as restricted dynamic range, hysteresis, reliance on consumables, transducer–sample interaction, and sample dispersion into the environment, are not easily overcome. In this paper, a non-dispersive Raman effect-based system is presented and compared with its dispersive alternative. This approach intrinsically guarantees no sample dispersion or preparation, as no direct contact is required between the sample and the transducer. Moreover, the technique does not suffer from hysteresis and recovering time issues. The results, evaluated in terms of sample pressures and camera integration time, demonstrate promising signal-to-noise ratio (SNR) and limit of detection (LOD) values, indicating strong potential for direct field application.